Environmental Conflict Communication PBNU and Activist Perspectives on Mining in Raja Ampat: A Discourse Analysis of the ROSI Kompas TV Broadcast - Nasution, Aditya Kurniawan (International Journal of Environmental Communication (ENVICOMM), 2025)
Environmental communication, critical discourse analysis, religious institutions, ecological justice, media framing, epThis study explores the dynamics of environmental conflict communication between religious institutions and civil society activists through a critical discourse analysis of the televised debate on ROSI Kompas TV, focusing on nickel mining in Raja Ampat. Using Fairclough’s model of Critical Discourse Analysis (CDA), which comprises three levels—text, discursive practice, and social practice—this research investigates how Ulil Abshar Abdalla (representing PBNU) and activist Iqbal Damanik construct opposing narratives regarding the involvement of religious organizations in mining projects. PBNU frames the mining initiative as a form of “public benefit” and national development, while the activist emphasizes ecological justice and the protection of indigenous rights. The analysis reveals how language, diction, metaphors, and interruption strategies are employed to establish both legitimacy and resistance. Additionally, the role of media is shown to be central in framing and selecting narratives, often marginalizing the voices of directly affected indigenous communities. This study contributes to the growing field of environmental communication in Indonesia by demonstrating how ecological conflicts are constructed and contested within mainstream public discourse.